1961
DOI: 10.3181/00379727-108-26988
|View full text |Cite
|
Sign up to set email alerts
|

Hexosamine and Hydroxyproline Alterations in Chronically Sun-Damaged Skin.

Abstract: ALTERATIONS IN SUN-DAMAGED SKIN 533cally affected gargoyles excrete significantly increased quantities of mucopolysaccharide. The known carriers and most of the siblings are in or near the normal range. Based on these quantitative data it is not yet possible to identify carriers by these procedures.Since the analytical methods employed yield values for total mucopolysaccharide without distinguishing among the various types which may be present, the present results do not preclude the existence of qualitative d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

1962
1962
2003
2003

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Skin thickness, primarily a measure of the integrity of the dermis, has been shown to diminish with age after the seventh decade of life, 10–12 and it has been suggested that this loss of dermal volume reflects a linear decline in dermal collagen content throughout life 13 . This collagen loss, confirmed with biochemical 14 and immunohistochemical 15 collagen assays, is even greater in photodamaged skin than in simply intrinsically aged skin 15 . Aged skin, lacking in tensile strength because of profound alterations in dermal collagen content, could be expected to be much less able to resist mechanical deformation than younger skin.…”
Section: Discussionmentioning
confidence: 80%
“…Skin thickness, primarily a measure of the integrity of the dermis, has been shown to diminish with age after the seventh decade of life, 10–12 and it has been suggested that this loss of dermal volume reflects a linear decline in dermal collagen content throughout life 13 . This collagen loss, confirmed with biochemical 14 and immunohistochemical 15 collagen assays, is even greater in photodamaged skin than in simply intrinsically aged skin 15 . Aged skin, lacking in tensile strength because of profound alterations in dermal collagen content, could be expected to be much less able to resist mechanical deformation than younger skin.…”
Section: Discussionmentioning
confidence: 80%
“…The impression engendered by histochemistry, and very likely the large losses of collagen reported in the early biochemical studies (3,4), have led to the perpetuation of inaccurate beliefs despite recent biochemical evidence to the contrary (5,6). ''Massive'' loss of collagen does not occur.…”
Section: Discussionmentioning
confidence: 99%
“…Biochemical verification of reduction in the collagen content of sun-damaged skin was first reported by Smith et al (3,4) in the early 1960's. Skin taken from forearms or necks of long-term residents of central Florida exhibited an average decrease of ∂45% in hydroxyproline content compared to cadaver skin from protected areas.…”
mentioning
confidence: 88%
See 1 more Smart Citation
“…19 In addition, a statistically significant decrease (20%) in total collagen content of sun-damaged skin versus sun-protected skin has been demonstrated 17 and confirmed in other studies. 20,21 Further investigation has shown that although collagen production remains unchanged, there is increased collagen degradation in sun-damaged skin, thus resulting in a net decrease in steady-state collagen levels, predominantly within the papillary dermis. 22 UV exposure has been shown to stimulate collagenase production directly by human fibroblasts 23 and to up-regulate collagenase gene expression.…”
Section: Introductionmentioning
confidence: 98%